The Republic of Texas - Oates, Stephen B.; Texas State Historical Association (Palo Alto, Calif., American West Pub. Co., 1968)
This book appears in May, 1968, in the year of the Southwest's first world fair - the HemisFair in San Antonio. San Antonio, situated as it is at a confluence of cultures, in many ways represents Texas as completely as any city in the state. It was a seat of government when Spain controlled Texas; it remained a seat of government when Mexico took over. Both Texas and Mexican armies fought over it; each won, and each lost the city. At the time of independence it was Texas's largest city, almost totally Mexican in population; and in San Antonio, or Bejar, the Alamo was besieged until it became a symbol for heroic resistance.
Preface, by J.B. Connally.--The Lone Star mystique, by J.B. Frantz.--Flag of illusion, by C. Robinson.--Myths and realities of the Alamo, by W. Lord.--Let us attack the enemy and give them hell! By N.D. Labadie; edited by S.B. Oates.--The Texas navy, by J.H. Jenkins.--Life in the land of beginning again, by W. Gard.--The Mexican War: climax of manifest destiny, by D. Lavender.--Documents of the Republic.--Literature of the Republic, by S.B. Oates.
Part of the illustrative matter is colored.
Bibliographical references included in "Literature of the Republic" (p. 80).
Keywords: Texas -- History -- Republic, 1836-1846.; Texas; Texas -- History -- Republic, 1836-1846.; 1836-1846; History